Coordination, organizations, institutions, and norms in agent systems XI : COIN 2015 International Workshops, COIN@AAMAS, Istanbul, Turkey, May 4, 2015, COIN@IJCAI, Buenos Aires, Argentina, July 26, 2015, Revised selected papers /: COIN 2015 International Workshops, COIN@AAMAS, Istanbul, Turkey, May 4, 2015, COIN@IJCAI, Buenos Aires, Argentina, July 26, 2015, Revised selected papers. (2016) - Unknown
No abstract available